Extraskeletal Osteosarcoma Misdiagnosed as Chondroma: A Case Report - Dalar, Sevda; Aydın, Özge (Asian Pacific Journal of Cancer Care, 2024)
Extraskeletal osteosarcoma is a rare malignant chondro-osseous neoplasm that arises outside the skeletal system. It accounts for less than 1% of all soft tissue sarcomas. We report a case of a 60-year-old male who presented with an isolated, primary subcutaneous tumor on the dorsal aspect of his left foot. Radiological imaging initially suggested an extraskeletal chondroma. However, following surgical excision and pathological analysis, the diagnosis of extraskeletal osteosarcoma was confirmed. This report describes the clinical and pathological findings of extraskeletal osteosarcoma in this case.